Tax Administration and Local Revenue Performances in Lira District Local Government - Otile, Milton; Akello, Judith Abal; Oguti, Robert Etengu (Lira University, 2022)
The study is to assess the effects of tax administration on Local performances in Lira district local government. The study’s objective were to asses the effect of tax identification on LDLG’s local revenue performances; and to assess the effect of tax collection procedures on LDLG’s local revenue performances. A descriptive study design and quantitative approach was used in the study. The study population was 65 people, and the sample size was 62 people, which was chosen using a purposive and random sampling technique. Key findings revealed that the effect of tax identification on local revenue performances in LDLG’s produced an adjusted R 2 of 0.587 which means that about 59% of the variations in Local Revenue performances can be explained by tax identification., the effect of tax assessment on local revenue performances in LDLG, the study produced an adjusted R 2 of 0.795 which means that about 80% of the variations in local revenue performances can be explained by tax assessment. The effect of tax collection procedures on local revenue performances in LDLG the study produced an adjusted R 2 of 0.721 which means that about 72% of the variations in local revenue performances can be explained by tax collection procedures. The study concluded that tax identification significantly affects local revenue performances, tax assessment significantly affects local revenue performances and tax collection procedures significantly affect local revenue performances. The study recommended Lira district local government to enhances its tax administrative policy specifically in tax identification, tax assessment and tax collect procedures, secondly LDLG should involve taxpayers more fully in the tax policy formulation process, restoring ownership and public confidences in the tax system. Keywords Tax Administration, Local Revenue Performances
Keywords: Tax Administration; Local Revenue Performances